Going green: Estimating the potential of green jobs in Argentina - Pablo de la Vega; Natalia Porto; Manuela Cerimelo (Journal for Labour Market Research, 2024)
This paper aims to identify and characterize the potential of green jobs in Argentina, i.e., those workers that would benefit from a transition to a green economy, using occupational green potential scores calculated in US O*NET data for the period 2015-2021. We apply the greenness scores to Argentine household survey data and estimate that between 23 and 25 percent of workers are in green jobs, i.e., have a high green potential. However, to promote and ensure an inclusive and effective green transition, we consider the decent work dimension (through legal informality measures), and find that between 11 and 12 percent of wage earners are in green formal jobs. We then analyze the relationship between the green job indicators and various labor and demographic variables at the individual level. We find that the green potential is relatively greater for men, the elderly, those with very high qualifications, and those in specific sectors such as construction, transportation, mining, and industry. These are the groups that are likely to be the most benefited by the greening of the Argentine economy. The green potential score is positively associated with informality, thus the green transition may be incompatible with decent work.
Keywords: E20; J80; Q50; 330; Argentina; Green jobs; Labor markets